2016
DOI: 10.1016/j.corsci.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

On the oxidation behavior of (Zr,Nb)2Fe under simulated nuclear reactor conditions

Abstract: The corrosion behavior of Zr alloys was affected by second phases, especially by those containing Fe and Nb. Ti 2 Ni-type (Zr,Nb) 2 Fe compound was melted and exposed to H 2 O 2 water solution at 320 °C and 16.4 MPa for 60 hours. The oxide layer was analyzed by X-ray diffraction and high-resolution transmission electron microscope (HRTEM). The formation of nano-crystalline tetragonal ZrO 2 (Fe-rich area) and amorphous ZrO 2 (Fe-deficient area) was observed. HRTEM analysis identified α-Fe could stabilize tetrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Elevated concentrations of Fe have been recorded at grain boundaries in the metal, which can continue into the oxide for at least 70 nm [20], therefore a similar distribution may be expected throughout the protective layer of the oxide. α-Fe has also been observed in corroded Zr intermetallic samples and shown to have the ability to stabilise tetragonal ZrO 2 [21]. The corrosion resistant properties of Fe has also been demonstrated in Zr(Fe,Nb) 2 in the C14 Laves phase, where it is suggested that the charge diversity of Fe promotes the formation of a layered oxide structure, within which the Fe-deficient layers provide a barrier for oxygen transport [22].…”
Section: Introductionmentioning
confidence: 96%
“…Elevated concentrations of Fe have been recorded at grain boundaries in the metal, which can continue into the oxide for at least 70 nm [20], therefore a similar distribution may be expected throughout the protective layer of the oxide. α-Fe has also been observed in corroded Zr intermetallic samples and shown to have the ability to stabilise tetragonal ZrO 2 [21]. The corrosion resistant properties of Fe has also been demonstrated in Zr(Fe,Nb) 2 in the C14 Laves phase, where it is suggested that the charge diversity of Fe promotes the formation of a layered oxide structure, within which the Fe-deficient layers provide a barrier for oxygen transport [22].…”
Section: Introductionmentioning
confidence: 96%
“…It should be noted that the acceptable error margin for XPS should be within 0.2 eV. 20 As shown in Fig. 6, the different treatments did not generate a reduced state of Ti.…”
Section: Resultsmentioning
confidence: 80%
“…The crystal phase of the NiCo 2 O 4 @MnO 2 structure was analysed by X-ray diffraction analysis (XRD), as shown in Figure 2. For the XRD pattern of NiCo 2 O 4 @MnO 2 , the broad and weak peaks indicated a poor crystallinity (Hu et al, 2016a(Hu et al, , 2016c. For the XRD pattern of NiCo 2 O 4 @MnO 2 , several characteristic peaks of 36.7°, 44.6° and 64.9°correspond to the respective (311), (400) and (440) planes, which can be well indexed to the spinel NiCo 2 O 4 phase (JCPDF card no.…”
Section: Resultsmentioning
confidence: 99%